An Investigation of Selected Socio-Demographic Factors with Aplastic Anemia in Pakistan: A Case-Control Study - Syed MA (Dove Medical Press, 2021)
Muhammad Asif Syed,1 Aneela Atta Ur Rahman,2 Abdul Ghani,3 Muhammad Nadeem Shah Syed,4 Muhammad Ilyas Siddiqui,2 Hina Riaz,5 Feriha Fatima Khidri,6 Nayyar Nawaz Baloch1 1Field Epidemiology Laboratory Training Program (FELTP), Karachi, Pakistan; 2Department of Community Medicine & Public Health Sciences, Liaquat University of Medical and Health Sciences, Jamshoro, Pakistan; 3Department of Health, Jam Ghulam Qadir Government Teaching Hospital, Hub, Pakistan; 4National Emergency Operation Center, National Stop Transmission of Polio (N-STOP), Islamabad, Pakistan; 5Department of Physiology/Medical Research Centre, Liaquat University of Medical and Health Sciences, Jamshoro, Pakistan; 6Medical Research Centre, Bilawal Medical College, Jamshoro, PakistanCorrespondence: Muhammad Asif SyedField Epidemiology Laboratory Training Program (FELTP), Karachi, Sindh, PakistanTel +0092-333-286-34-77Email asif.mph@gmail.ccomIntroduction: In Pakistan, the incidence rate of aplastic anemia is 3.5 cases/million. The associated risk factors are exposure to pesticides, chemicals, and some drugs. The link between aplastic anemia and socio-demographic factors is debatable.Purpose: We conducted this study to investigate the role of socio-economic and -demographic factors with aplastic anemia.Methodology: A total of 191 lab-confirmed incident cases of aplastic anemia were identified from the tertiary hospital of Karachi-Pakistan in between 2015 and 2018. Age and gender-matched 694 controls were randomly selected from the same institute admitted or visited for other non-neoplastic conditions. Socio-demographic and exposure information was gathered using a data collection form. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were computed for selected socio-demographic factors.Results: Among socio-demographic factors, significant associations of aplastic anemia risk emerged for illiteracy (aOR: 2.3; 1.5; 3.5) occupation (any type) (aOR: 2.1; 1.7; 2.5), living in rural environments (aOR: 2.9; 1.9; 4.2). The odds of aplastic anemia increased with the age group 31– 50 years (aOR: 1.8; 1.7; 3.5) and > 50 years (aOR: 2.5; 2.1; 4.2). We observed no association of income with the risk of aplastic anemia.Conclusion: This study highlights the importance of socio-demographic factors as a risk factor for the development of aplastic anemia in the population of Pakistan. In order to reduce disease incidence, health education program and use of personal protective equipment and organization of screening camps in high-risk population is warranted.Keywords: aplastic anemia, Socio-demographic factors, case-control study, Pakistan